Jews in Poland-Lithuania in the eighteenth century : a genealogy of modernity - Hundert, Gershon David, 1946-2023 (University of California Press, 2004)
Annotation A history of Jews in Poland-Lithuania in the eighteenth century which argues that this largest Jewish community in the world at that time must be at the center of consideration of modernity in Jewish history.
Keywords: Jews -- Poland -- History -- 18th century.; Jews -- Poland -- Economic conditions -- 18th century.; Jews -- Poland -- Social conditions -- 18th century.; Jews -- Lithuania -- History -- 18th century.; Jews -- Lithuania -- Economic conditions -- 18th century.; Jews -- Lithuania -- Social conditions -- 18th century.; Mysticism -- Judaism -- History -- 18th century.; Hasidism -- Europe, Eastern -- History -- 18th century.; Poland -- Ethnic relations.; Lithuania -- Ethnic relations.; Juifs -- Pologne -- Histoire -- 18e siècle.; Juifs -- Pologne -- Conditions économiques -- 18e siècle.; Juifs -- Pologne -- Conditions sociales -- 18e siècle.; Juifs -- Lithuanie -- Histoire -- 18e siècle.; Juifs -- Lituanie -- Conditions économiques -- 18e siècle.; Juifs -- Lituanie -- Conditions sociales -- 18e siècle.; Mysticisme -- Judaïsme -- Histoire -- 18e siècle.; Hassidisme -- Europe de l'Est -- Histoire -- 18e siècle.; Pologne -- Relations interethniques.; HISTORY -- Europe -- Germany.; RELIGION -- Judaism -- General.; Ethnic relations; Hasidism; Jews; Jews -- Economic conditions; Jews -- Social conditions; Mysticism -- Judaism; Eastern Europe; Lithuania; Poland; Soziale Stellung; Chassidismus; Mystik; Polen; Litauen; Joden.; Culturele identiteit.; Juden -- Litauen -- Geschichte 18. Jh.; Juden -- Polen -- Geschichte 18. Jh.; Juden -- Polen -- Geschichte -- 1700-1800.; Polen -- Juden -- Geschichte -- 1700-1800.; Juden -- Litauen -- Geschichte -- 1700-1800.; Litauen -- Juden -- Geschichte -- 1700-1800.; Żydzi -- Litwa -- 18 w.; Żydzi -- Polska -- 18 w.; Mniejszości narodowe -- Litwa -- 18 w.; Mniejszości narodowe -- Polska -- 18 w.; Chasydyzm -- historia -- Litwa -- 18 w.; Chasydyzm -- historia -- Polska -- 18 w.; Kościół katolicki -- a Żydzi -- Polska -- 18 w.; Litwa -- stosunki etniczne -- 18 w.; Polska -- stosunki etniczne -- 18 w.; Juden.; 1700-1799; Poland -- Ethnic relations; Lithuania -- Ethnic relations -- Litauen (Großfürstentum) -- Juden -- Geschichte 1700-1800; Polen -- Juden -- Geschichte 1700-1800; History